2017
DOI: 10.1080/13548506.2017.1280176
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of burnout and health status in Samaritans’ listening volunteers

Abstract: Samaritan listening volunteers provide emotional support to people in distress or suicidal. Samaritans' has high volunteer turnover, which may be due to burnout. This study evaluated the role of demographic and psychosocial factors in predicting Samaritans listening volunteers' burnout and health status. Samaritans' listening volunteers (n = 216) from seven branches across UK completed an online survey to assess their levels of burnout (emotional exhaustion, depersonalisation, personal accomplishment), subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 19 publications
(26 reference statements)
1
24
0
1
Order By: Relevance
“…Only thirteen studies, published between 1973 and 2018, were included in the current review: eight quantitative surveys [27][28][29][30][31][32][33][34] and five qualitative studies (observation, participation, document study, and interviews) [35][36][37][38][39]. No clinical trials or longitudinal studies were found.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Only thirteen studies, published between 1973 and 2018, were included in the current review: eight quantitative surveys [27][28][29][30][31][32][33][34] and five qualitative studies (observation, participation, document study, and interviews) [35][36][37][38][39]. No clinical trials or longitudinal studies were found.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The quality of the studies varied widely. Only four of the eight surveys used validated instruments to assess mental wellbeing or the factors influencing mental wellbeing [28,30,33,34]. The other four surveys used a single item to measure subjective mental wellbeing [27,29,31,32].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations